2013
DOI: 10.1186/1471-2288-13-86
|View full text |Cite
|
Sign up to set email alerts
|

OvidSP Medline-to-PubMed search filter translation: a methodology for extending search filter range to include PubMed's unique content

Abstract: BackgroundPubMed translations of OvidSP Medline search filters offer searchers improved ease of access. They may also facilitate access to PubMed’s unique content, including citations for the most recently published biomedical evidence. Retrieving this content requires a search strategy comprising natural language terms (‘textwords’), rather than Medical Subject Headings (MeSH). We describe a reproducible methodology that uses a validated PubMed search filter translation to create a textword-only strategy to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 11 publications
(11 reference statements)
0
12
0
Order By: Relevance
“…Careful and accurate translation of searches between interfaces is required since search interface options and search syntax vary (Harbour et al, 2014). Searching guidelines recommend that translation is undertaken carefully (Centre for Reviews and Dissemination, 2009;Lefebvre, Manheimer & Glanville, 2011), and the process has been shown to be complex (Beynon et al, 2013;Damarell, Tieman & Sladek, 2013;McGowan et al, 2016;Wood, Glanville, Wright & Arber, 2017) and require care and testing (Damarell et al, 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Careful and accurate translation of searches between interfaces is required since search interface options and search syntax vary (Harbour et al, 2014). Searching guidelines recommend that translation is undertaken carefully (Centre for Reviews and Dissemination, 2009;Lefebvre, Manheimer & Glanville, 2011), and the process has been shown to be complex (Beynon et al, 2013;Damarell, Tieman & Sladek, 2013;McGowan et al, 2016;Wood, Glanville, Wright & Arber, 2017) and require care and testing (Damarell et al, 2013).…”
mentioning
confidence: 99%
“…Research has shown that translators should take care because interface differences can impact on retrieval (Damarell et al, 2013;Neyt & Chalon, 2013). Authors have also provided algorithms (macros) to automate the conversion of search strategies between interfaces (Bramer, Rethlefsen, Mast & Kleijnen, 2017).…”
mentioning
confidence: 99%
“…Equivalence testing confirmed the performance of the OvidSP filter in the PubMed database following translation for PubMed syntax. In addition, a specific text word version of the filter was developed to ensure that the not‐yet‐indexed citations in PubMed could also be searched . These two models were combined to form the final PHC Search Filter, which searches PubMed's indexed (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, a specific text word version of the filter was developed to ensure that the not-yet-indexed citations in PubMed could also be searched. 19 These two models were combined to form the final PHC Search Filter, which searches PubMed's indexed (i.e. Medline citations indexed with MeSH terms), unindexed (i.e.…”
Section: Stage 2: Enhancing Functional Utility Through Web-based Accessmentioning
confidence: 99%
“…For aiding translation across databases, Damarell et al used text mining to capture items from PubMed not indexed with controlled Medical Subject Headings; however, this could have wider applications in assisting development of search strategies across other databases. The reverse of this approach is also used where citations identified from searches of free‐text fields in a database are analysed for suitable controlled vocabularies.…”
Section: An Overview Of Applications Of Text Mining For Search Term Dmentioning
confidence: 99%